Burdens of Tracheal, Bronchus, and Lung Cancer From 1990 to 2021 in China Compared to the Global Projection of 2036: Findings From the 2021 Global Burden of Disease Study - Yuxing Chen; Qingpeng Zeng; Muyu Li; Jiahui Jin; Jun Zhao (Thoracic Cancer)
ABSTRACT Background Tracheal, bronchial, and lung cancers (TBL cancers) pose a significant global health challenge, with rising incidence and mortality rates, particularly in China. Studies from the Global Burden of Disease (GBD), 2021, can guide screening and prevention strategies for TBL cancer. This study aims to provide a comprehensive analysis of the burden of TBL cancers in China compared to global data. Methods We conducted an analysis of incidence, prevalence, mortality, and disability‐adjusted life years (DALYs) from 1990 to 2021. We also performed Joinpoint regression analysis and Bayesian age‐period‐cohort (BAPC) modeling to project future trends. Results From 1990 to 2021, there was a substantial increase in TBL cancer indicators for all sexes in China, with the most significant rise observed in females. The female population showed alarming increases in age‐standardized incidence rate (ASIR) and age‐standardized prevalence rate (ASPR). While global efforts have managed to stabilize these rates, China's figures remain high, suggesting the impact of persistent risk factors such as smoking and air pollution, coupled with an aging population. Furthermore, we utilized the projection model in China to estimate that these indicators of TBL cancers in females will likely follow continuous and rapid upward trends, while the burden of TBL cancers among males is expected to have a steady trend. Conclusion Although global efforts have been effective in reducing the burden of TBL cancers over the past three decades, there still remains strong regional and gender heterogeneity. TBL cancers need more screening strategies and medical attention in China and in the female population.